The Dynamics of Teacher Performance Assessment on Teacher Discipline: A Case Study at SDN Plompong 02, Brebes Regency - Latief Assidiq; Sri Susilogati Sumarti (Universitas Negeri Semarang, 2025)
This study was motivated by the disparity between the high formal results of the Teacher Performance Assessment (PKG) and the reality of low teacher discipline in the field, specifically at SDN Plompong 02, Sirampog District, Brebes Regency. This qualitative case study aims to analyze the dynamics of the relationship between the implementation of PKG and the level of teacher discipline. Data were collected through in-depth interviews with the principal, teachers, and school supervisors, participant observation, and documentation studies. Data analysis followed the interactive model of Miles and Huberman. The findings indicate that: (1) PKG at SDN Plompong 02 is implemented systematically, transparently, and is oriented towards continuous coaching; (2) Teacher discipline is high, demonstrated through punctuality, attendance, and task responsibility; (3) There is a significant reciprocal relationship between PKG and teacher discipline, where PKG functions as an effective motivational and control instrument for shaping disciplined behavior, while good discipline facilitates optimal performance achievement; (4) The success of this relationship is supported by the principal's transformational leadership, exemplary behavior, dialogical communication, and a conducive organizational culture. The study concludes that PKG, implemented with a coaching and humanistic approach and supported by effective leadership, can be a primary driver for improving teacher discipline and professionalism. This research contributes to the development of a holistic and contextual teacher performance management model, especially for elementary schools in rural areas.